Study on cyclic variation rate of fuel flow in the nozzle during fuel injection. Issue 3 (September 2021) - Hua, Wen; Xin-yu, Zhang; Yu-long, Jiang; Ling-yao, Zhao
The fuel flow pattern in the fuel injection nozzle of diesel engine is a complex and changeable phenomenon, which is easily affected by various factors, bringing the differences of flow patterns between multiple injection cycles. To solve the above problem, a visual experimental platform of fuel injection nozzle was built, in which the 100 injection cycles of diesel engine on the same working condition were photographed via shadowgraphy to study the difference in fuel flow pattern in the nozzle by ensemble average processing method. The cyclic variation rate K of fuel flow pattern is defined. Results demonstrate that the fuel flow pattern tends to be the same in multiple fuel injection cycles, but there is a strong randomness at the starting of injection and after ending of injection; the K can be reduced by decreasing the injection pressure and the inclination angle of orifice, so that the fuel flow pattern in the nozzle tends to be consistent.